2009
DOI: 10.1104/pp.109.142059
|View full text |Cite
|
Sign up to set email alerts
|

The Grapevine R2R3-MYB Transcription Factor VvMYBF1 Regulates Flavonol Synthesis in Developing Grape Berries

Abstract: Flavonols are important ultraviolet light protectants in many plants and contribute substantially to the quality and healthpromoting effects of fruits and derived plant products. To study the regulation of flavonol synthesis in fruit, we isolated and characterized the grapevine (Vitis vinifera 'Shiraz') R2R3-MYB transcription factor VvMYBF1. Transient reporter assays established VvMYBF1 to be a specific activator of flavonol synthase1 (VvFLS1) and several other promoters of grapevine and Arabidopsis (Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
396
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(429 citation statements)
references
References 86 publications
20
396
2
4
Order By: Relevance
“…The spatial and temporal patterns of Vv GT5 and Vv GT6 cDNA expression were very similar and resembled those of Vv FLS1. These results, along with the fact that Vv GT5 and Vv GT6 genes are located in proximity to one another on the same chromosome, strongly suggest that expression of these two UGT genes is coordinately controlled by common transcription factors in grapevines, which probably include the flavonol-specific MYB transcription factor Vv MYBF1 (Czemmel et al, 2009). …”
Section: Functional Significance Of Vv Gt5 and Vv Gt6 In Biosynthesismentioning
confidence: 80%
See 2 more Smart Citations
“…The spatial and temporal patterns of Vv GT5 and Vv GT6 cDNA expression were very similar and resembled those of Vv FLS1. These results, along with the fact that Vv GT5 and Vv GT6 genes are located in proximity to one another on the same chromosome, strongly suggest that expression of these two UGT genes is coordinately controlled by common transcription factors in grapevines, which probably include the flavonol-specific MYB transcription factor Vv MYBF1 (Czemmel et al, 2009). …”
Section: Functional Significance Of Vv Gt5 and Vv Gt6 In Biosynthesismentioning
confidence: 80%
“…The results were compared with those of Vv GT1 (Ford et al, 1998), which is responsible for anthocyanin biosynthesis in grapevine berry skin and Vv FLS1 (also termed Vv FLS4), which is responsible for flavonol biosynthesis (Fujita et al, 2006;Czemmel et al, 2009) (Figure 3, left panels). The Vv GT5 transcript was abundant in berry skin and increased at the onset of pigmentation (veraison), with the highest level of transcription detected in the fully pigmented skin (exocarp) of mature berries ( Figure 3, second panel).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…2B), was selected to generate a lar1/lar1 homozygous NIL for subsequent transgenic experiments and gene expression analysis. This subgroup of MYB transcription factors is known to regulate flavonol biosynthesis in Arabidopsis, grapevine, and tomato (19)(20)(21)(22), and regulate the biosynthesis of 3-deoxyflavonoids and phlobaphenes in maize (23). Both flavonol and anthocyanin biosynthesis require the same intermediate substrate, dihydroflavonol.…”
Section: Resultsmentioning
confidence: 99%
“…These factors can activate an ABREcontaining promoter in an ABA-dependent manner (Uno et al, 2000). However, the involvement of the ABREbinding bZIP TFs in Myb TF expression regulating flavonoid biosynthesis has not yet been demonstrated, although bZIP TFs have been suggested to directly affect the expression of some flavonoid pathway genes such as FLS in Arabidopsis and grapevine (Hartmann et al, 2005;Czemmel et al, 2009;Hichri et al, 2011). Our study showed that ABA signals can act as a regulator of DkMyb4 and the resultant PA biosynthesis via the activity of ABF/AREB/ABI5-like bZIP TFs in specific developmental stages of persimmon fruit.…”
mentioning
confidence: 99%